0002 Leptin Receptor Positive Neurons In The Dorsomedial Hypothalamus Maintain Upper Airway Patency During Sleep. (12th April 2019) - Pho, Huy; Berger, Slava; Freire, Carla; Dergacheva, Olga; Curado, Thomaz Fleury; Schwartz, Alan R; Mendelowitz, David; Polotsky, Vsevolod Y
Abstract: Introduction: Both deficiency of adipocyte-produced hormone leptin and resistance to leptin's effects cause obstructive sleep apnea (OSA) and obesity hypoventilation syndrome (OHS), which are reversed by leptin delivery to the brain. However, mechanisms of leptin's effect on sleep disordered breathing remain unknown. We previously shown a retrograde neuronal tracer pseudorabies virus injected in the genioglossus muscle of the tongue spreads to the dorsomedial hypothalamus (DMH), which abundantly expresses leptin receptor LepR b . We hypothesized that LepR b+ neurons in DMH project to the hypoglossal motoneurons and upon excitation with leptin activate these neurons to prevent OSA. Methods: LepR b deficient db/db mice (15.9±0.3wks, 49.1±0.7g, n=20) underwent stereotactic administration of adenovirus harboring LepR b ( Ad-LepR b ) or green fluorescent protein ( Ad-GFP ) in DMH. An intracerebroventricular (ICV) catheter was inserted into the lateral ventricle of mice implanted with EEG/EMG leads. Polysomnography was performed 9 and 12 days after surgery, and hypercapnic ventilatory response (HCVR, 8%CO2 ) during NREM sleep, both with or without ICV leptin (10µg/2µl). Upper airway obstruction was defined by the presence of inspiratory airflow limitation (IFL), characterized by early inspiratory plateau in airflow at a maximum level (VI max) while effort continued to increase. For optogenetics, LepR b -Cre mice were crossed to channelrhodopsin (ChR2) floxed mice and brains were harvested at 21 days. Results: At baseline, db/db mice infected with Ad-GFP and Ad-LepR b showed severe OSA in REM sleep (55±5% IFL). Leptin had no effect on breathing in Ad-GFP mice. In contrast, in Ad-LepR b mice, leptin significantly decreased IFL during REM sleep (8±3%, p<0.001) and increased minute ventilation (VE ) and VI max during IFL breathing in NREM and REM sleep. Leptin did not affect the HCVR in both groups. LepR b was predominantly expressed in neurons and not in astrocytes, and LepR b+ cells were nearly uniformly melanocortin receptor 4(+). Optogenetic studies showed that while hypoglossal motoneurons lacked LepR b, LepR b+ fibers projected extensively to these cells. Optogenetic stimulation of DMH activated hypoglossal motoneurons. Conclusion: Leptin acts upon LepR b (+) neurons in DMH which project to the hypoglossal motoneurons and maintains upper airway patency during sleep. Support (If Any): 5R01HL128970-04